Rabbit Farming Management Practices: A Case Of An Emerging Rabbit Farmer/Producer - Nerisa Paladan (International Journal of Science and Environment (IJSE), 2022)
Promoting rabbit (Oryctolagus cuniculus) farming responses to the challenges in food security and agricultural sustainability. The purpose of this study is to describe the management practices of emerging rabbit farmers/producers in rural areas in relation to their housing practices, feeding, breeding, and healthand disease management. Also, it identifies the benefit and challenges of rabbitfarming. Furthermore, a framework was developed in capacitating the rabbitfarmers/producers to make rabbit farming ventures a sustainable livelihood in rural areas. Descriptive research was utilized; 33 rabbit farmers are the respondents of this study; a snowball sampling technique was used to identify the respondent. In- depth semi-structured interviews and observation were used in gathering the data. Findings revealed that farmers invest in galvanized wire cages but some use local materials like bamboo and used wood however they need to improve their housing design even its backyard rabbit raising. The majority uses a combination of rabbit pellets & forages that are locally available for feeding the rabbit. Also, most of them acquire their rabbit breed from local rabbit breeders where the challenge to the farmers is the quality and the inbreeding. Skin disease and diarrhea are common diseases in rabbits andfarmers have knowledge of identifying the symptoms and also curing them. Themajor benefit of rabbit production it gives an additional source of income forrabbit farmers/producers while the major challenges are inadequate/limited knowledge of rabbit production and an unreliable market for rabbit breeds and meat.